AKTIVITAS MEMANCING IKAN DALAM PERSPEKTIF SOSIOLOGI WAKTU LUANG - Pratama, Agus Elfa; Kamajaya, Gede; Nugroho, Wahyu Budi; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
ABSTRACT This research  focuses on the phenomenon of free time activities that people use to fish at Taman Pancing, Denpasar and also Kedonganan Pier, Kuta The aim of this research is to explain and analyze the use of free time that people use for fishing and its relationship to various aspects of life. The method used in this research is a qualitative approach with descriptive-explanatory research type. The theory chosen as a scalpel in analyzing research is the sociological leisure of John Wilson. The results of this research reveal that fishing is a leisure activity that is related to subjective personal pleasure and calm. Fishing activities carried out as a recreational medium by people in their free time ultimately have a strong relationship to several aspects such as work, family, life cycle and social stratification. Jobs in the informal sector tend to have more freedom to engage in fishing activities because working hours are less restrictive. Then occasionally anglers invite family members to spend free time together to continue fishing activities. The life cycle of someone with free time is influenced by economic factors, future career and also youthful enthusiasm. Furthermore, social stratification in fishing activities is more about how to fish and also equipment which tends to be expensive. Fishing by boat in the middle of the sea will be different from fishing only on the outskirts of town. The cost of fishing will be much more expensive by boat, followed by equipment that is also expensive compared to equipment for fishing on the outskirts